Reconnecting to Contemplation, Mission and Martyrdom during the Covid-19 Pandemic (The Macau Ricci Institute Journal, 2020)
The pandemic of COVID-19 has provoked massive economic crises and left many people wondering how they may manage to survive. In the midst of such a situation of profound uncertainty we may recognise a unique opportunity to reconnect to key issues of life and death which all too often risk being dismissed as a pure waste of time by people obsessed with money and power. As we experience a massive collapse of economic growth we need to welcome this moment as a wake-up call for reflection on what really counts in our lives.